Crashworthiness analysis of multi-configuration thin walled co-axial frusta tube structures under quasi-static loading. (September 2020) - Patel, Vivek; Tiwari, Gaurav; Dumpala, Ravikumar
Abstract: In the present study crashworthiness performance of monolithic and co-axial multi-wall (double, triple, and four layered) frusta tube structures was investigated under the quasi-static axial loading. The developed layered frusta tubular structures having a total equivalent thickness of 2.3 mm were made of aluminium alloy AA-1080 sheet. A series of layered configurations were simulated and analysed using non-linear finite element analysis code LS-DYNA, keeping volume approximately the same as the monolithic frusta tube. For the effectiveness of the simulated results, double-tubular structure was examined through experimental results. A parametric study was performed by keeping taper angle constant as 5.71° with the variation in height (91.6 and 82 mm for double layered, 91.6, 86 and 78 mm for triple layered and 91.6, 87, 82 and 77 mm for four layered), thickness (2.3–0.4 mm) and diameter (smaller end diameter in the range of 42.8 mm–48.4 mm while larger end diameter varied from 61 mm to 64 mm) to analyse the crushing performance of layered structures. The crashworthiness performance indicator like peak force (PF), mean force (MF), energy absorbing capacity (EAC), specific energy absorption (SEA) and crush load efficiency (CLE) which is defined as the ratio of MF to the PF, were studied for the various layered frusta tubular structures. Moreover, optimization technique GRA (Grey Relational Analysis) was employed to obtain a better combination of multi-wall layered structures. With the increase in the layer, the initial peak force was reduced compared to the monolithic frusta. The optimization technique suggested the triple-layer configuration showed better crashworthiness performance. Highlights: Crushing response of double, triple and four layered frusta was investigated. Effectiveness of the layered frusta was shown by comparing with monolithic frusta. The results were optimized through the Grey Relational Analysis (GRA). Layered frusta showed lower peak force and higher CLE compared to monolithic. Triple layered frusta were found better performance among all studied structures.